POPULATION DENSITY AND VALUES OF AVENUE TREES: A CASE STUDY OF IBADAN METROPOLIS, OYO STATE, NIGERIA - Salami, K. D.; Akinyele, A. O. (FUDMA JOURNAL OF SCIENCES, 2020)
The assessment of avenue trees was investigated in six selected areas including: Are, Rotimi Williams, Familusi, Awosika, Awolowo, Osuntokun within Ibadan metropolis where twenty respondents were selected in each of the avenues. Well-structured questionnaires were distributed among the respondents. The result showed that most of the respondents were male (90%) while (10%) were female was noted in Osuntokun Avenue. It was noted that Islam and Christianity were the major religion of the respondents. The highest respondents marital status was in Rotimi Williams avenue with (80%) married among others. 90% respondents with tertiary school education experience was found in Osuntokun avenue. However, the avenues with highest population of tree density (58 and 54) were found in both Awosika and Awolowo avenues respectively. Eighty seven (87) were total trees species planted in the selected areas (avenues) that serve as aesthetic value among others. Most respondents (81) reported that they maintained the avenues
Keywords: Avenue trees, Values, Population Density, Ibadan metropolis